2022
DOI: 10.4018/978-1-6684-5231-8.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Edible Electronic Medical Devices and their Potential Application in the Medical Field

Abstract: Edible electronics presuppose the utilization of food ingredients to build various components of a fully functional sensor that can be consumed orally. The sensors stay inside the body for a particular time either to monitor physiological functions or treat diseases then transmit the information to a connected mobile phone. However, not all food components satisfy the criteria required for constructing a consumable sensor. Therefore, it is essential to thoroughly analyze the components before implementation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…Implanting electronic devices in the intestine is an emerging field that holds immense potential for improving the management of T2DM. These devices, including those commonly known as "smart pills" or "digestible sensors"[ 4 ], can be ingested orally and provide real-time monitoring and therapeutic interventions within the gastrointestinal tract[ 5 , 6 ]. Although the field of implantable electronic devices for T2DM treatment is still in its early stages, preliminary studies have demonstrated their safety and efficacy.…”
Section: Implanted Electronic Devices In the Intestine For The Treatm...mentioning
confidence: 99%
“…Implanting electronic devices in the intestine is an emerging field that holds immense potential for improving the management of T2DM. These devices, including those commonly known as "smart pills" or "digestible sensors"[ 4 ], can be ingested orally and provide real-time monitoring and therapeutic interventions within the gastrointestinal tract[ 5 , 6 ]. Although the field of implantable electronic devices for T2DM treatment is still in its early stages, preliminary studies have demonstrated their safety and efficacy.…”
Section: Implanted Electronic Devices In the Intestine For The Treatm...mentioning
confidence: 99%